Reinterpretation of Spanish planning on the eighties: Generation of plans, generations of urbanists (Ciudades, 2018)
The "plans of the eighties" are on their way to becoming a milestone on the history of current Soanish planning. A milestone that has its origin on two early articles by the professors J.J Trapero, "Characteristics of the new municipal planning" in 1985 and M. Solá-Morales and J. Parcerisa, "Urban urbanism" in 1987, in which there is a comparative study of the last general plans of Gijón, La Coruña, Madrid, Málaga, Pamplona, Salamanca, Tarragona, Valladolid and some other cities, evaluating their combined contributions.
Keywords: urban planning; '80s; urbanism